Association between the dietary inflammatory index, bowel habits, and systemic serum inflammatory markers: insights from NHANES (2005–2010) - Zhou, Zeyang; Li, Xiangyong; Xiong, Mengya; He, Yuee; Cheng, Xinmeng; Deng, Jianbo; Li, Yanan; Zhang, Xiaoyang; Zhang, Zhengcao; Zhou, Chenxi; Yang, Xiaodong (Frontiers in Nutrition, 2025)
ObjectiveTo examine the relationship between the Dietary Inflammatory Index (DII), abnormal bowel habits, and systemic serum inflammatory markers.MethodsData from 9,880 participants in the National Health and Nutrition Examination Survey (NHANES) 2005–2010 were analyzed. The DII was calculated from two 24-h dietary recalls. Bowel habits were assessed using the Bristol Stool Form Scale, and systemic inflammatory markers included AAPR, IBI, NLR, LMR, PNLR, LCR, LA, and PLR. Statistical analyses were performed using R, Zstats, and EmpowerStats to evaluate associations.ResultsHigher DII scores were positively associated with abnormal bowel habits, including constipation [β (95% CI): 0.11 (0.01–0.22)] and diarrhea [β (95% CI): 0.42 (0.32–0.53)], and with PNLR [β (95% CI): 0.01 (0.01–0.01)], PNLRQ4 [β (95% CI): 0.13 (0.05–0.20)], IBI [β (95% CI): 0.02 (0.01–0.02)], and IBIQ4 [β (95% CI): 0.33 (0.25–0.42)] (p < 0.05). Negative associations were found with AAPR [β (95% CI): −0.33 (−0.60 - −0.06)] and AAPRQ4 [β (95% CI): −0.18 (−0.34 - −0.01)], while no significant associations were observed with LA, LCR, or LMR. Subgroup analyses confirmed stable associations between DII and both chronic diarrhea and constipation across seven subgroups. Smoothed curve fitting revealed nonlinear relationships. A J-shaped association between DII and chronic constipation was identified in BMI and IBI subgroups. For BMI >30, the breakpoint (K) was 1.89, with ORs of 1.228 (95% CI: 1.097–1.375) below and 3.318 (95% CI: 1.531–7.191) above this point. In the IBI Q4 subgroup, the breakpoint was 1.96, with ORs of 1.145 (95% CI: 1.013–1.294) below and 5.794 (95% CI: 2.359–14.228) above. In the diarrhea group, a U-shaped association was observed in the AAPR Q4 population, with a breakpoint of −1.312 and ORs of 0.657 (95% CI: 0.478–0.901) below and 1.266 (95% CI: 1.057–1.518) above.ConclusionHigher DII scores are linked to an increased risk of chronic constipation and diarrhea and are associated with systemic inflammatory markers and factors such as BMI.